2006
DOI: 10.1111/j.1365-2516.2006.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in haemophilia – an underestimated comorbidity?

Abstract: A relationship between haemophilia and osteoporosis has been suggested, leading to the initiative for a larger study assessing this issue. Bone mineral density (BMD) was measured by osteodensitometry using dual energy X-ray absorptiometry (DEXA) in 62 male patients with severe haemophilia A; mean age 41 +/- 13.1 years, mean body mass index (BMI) 23.5 +/- 3.6 kg m(-2). Using the clinical score suggested by the World Federation of Hemophilia, all patients were assessed to determine the severity of their arthropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
6
13

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 23 publications
7
133
6
13
Order By: Relevance
“…Among them, more than a half (55.6%) had osteoporosis and the rest (30.5%) had osteopenia. Gallacher et al first reported a reduced BMD in 19 hemophilia patients [8], and recently, similar results had also been reported in a larger study with 62 hemophilia patients [9]. In that study, 70% of the patients had reduced BMD in the FN by DEXA evaluation.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Among them, more than a half (55.6%) had osteoporosis and the rest (30.5%) had osteopenia. Gallacher et al first reported a reduced BMD in 19 hemophilia patients [8], and recently, similar results had also been reported in a larger study with 62 hemophilia patients [9]. In that study, 70% of the patients had reduced BMD in the FN by DEXA evaluation.…”
Section: Discussionsupporting
confidence: 71%
“…The results from the studies that have investigated the impact of hepatitis C on osteoporosis of hemophilia patients are conflicting. In two studies [10,17], no difference in the severity of osteoporosis between HCV-positive and HCVnegative patients was observed, while in the study of Wallny et al [9], a significant difference in mean values of BMD was reported in the two groups. Almost all of the patients of our cohort were HCV-positive, and this could be considered as a factor implicated in the high incidence of osteoporosis observed in our study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Those results are comparable with findings of Nair, who described reduced bone mass in 50% of patients with severe haemophilia (Nair, 2007). On the other hand, some authors showed reduced bone mass in 86% patients with severe and moderate haemophilia (FVIII<3%) (Katsarou, 2009), and in 70% of patients with severe haemophilia (Gerstner, 2009, Wallny, 2007. The reason for difference between those results is uncertain.…”
Section: Incidence Of Reduced Bone Mass In Haemophilia Patientssupporting
confidence: 77%
“…They have to do functional training (hydrotherapy, walking climbing stairs, cycling, etc). Osteopenia and osteoporosis can cause increased number of serious injuries and fracture after falls (Wallny, 2007). Painful haemophilic arthropathy with reduced mobility and lack of activity may lead to a reduction of bone mass.…”
mentioning
confidence: 99%